Projections of Regional Macroeconomic Conditions using the Univariate Forecasting Method - Inayati Nuraini Dwiputri; Muhammad Syam Kusufi; Albertus Girik Allo (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2019)
The prediction of future macroeconomic conditions is needed by the government to carry out the planning and budgeting. This study predicts macro indicators in Hulu Sungai Utara Regency in the period 2017-2022. The method used is univariateforecasting, which includes the ARIMA model, exponential smoothing, and exponential smoothing with trend adjustment. The macroeconomic indicators used in this study are real Gross Domestic Regional Product (GDRP), economic growth, unemployment rate, and income distribution. The results of the analysis show that Brown's forecasting model is predicted that the real GDRP value tends to increase, forecasting results using a simple model on economic growth and the ARIMA (0.0,0) model on the unemployment rate, had predicted tends to be constant. And, the prediction of income distribution with the Holt model tends to increase. Keywords: macroeconomic, univariate, forecasting, ARIMA, exponential smoothing JEL Classification: E0, O1, C0